PENGARUH KETIDAKPASTIAN LINGKUNGAN DAN STRATEGI BISNIS TERHADAP SISTEM INFOMASI AKUNTANSI MANAJEMEN DENGAN TOTAL QUALITY MANAGEMENT SEBAGAI VARIABEL INTERVENING - uum helmina chaerunisak (AKUNTANSI DEWANTARA, 2017)
ABSTRACT This study aims to test the influence of uncertainty the environment and business strategy against the system information accounting management with a total quality management (TQM ) as variable no intervening. This research consisting of two exogenous, one variable endogenous, and one variable no intervening. Exogen variable in this research was uncertainty the environment and business strategy measured by indicators of items questions in the questionnaire.Variable endogenous in this research was information system accounting management.Variable no intervening is TQM. This study used purposive sampling. Used as a sample of 60 respondents in the motor vehicle trade service company in DIY. Research data analysis using Structural Equation Model - Partial Least Square (PLS-SEM) with WARP-PLS.Based on the results of the analysis indicate that the first hypothesis testing uncertainties affect the TQM environment. The second hypothesis does not affect the business strategy of TQM. The third hypothesis TQM influence on management accounting information systems. The fourth hypothesis environmental uncertainty influence on management accounting information system. Hypothesis fifth business strategy does not affect the accounting information system management. Environmental uncertainties sixth hypothesis indirectly significant effect on management accounting information systems to be mediated in part (partial) by the Total Quality Management (TQM). Hypothesis seventh business strategy does not significantly influence the management accounting information system of Total Quality Management (TQM) does not act as a mediator. Keywords: environmental uncertainty, business strategy, Total Quality Management, management accounting information system